Isolation and Identification of Yeasts from Indoor Swimming Pools in Duhok City With Special Concern to The Effect of Some Disinfectant Agents - Abdullah, Berivan A.; Saadullah, Asia A.M. (Science Journal of University of Zakho, 2017)
The present study was conducted to study the level of yeast contamination in indoor public swimming pools in Duhok city. A total of 230 samples (50 water sample) were taken from swimming pool water and (180 swab samples) were taken from walls, flour of bathrooms, dressing rooms and flour around the pool in five indoor public swimming pools from September 2014 to February 2015. All samples were examined for the presence of yeasts using three culture media (Potato Dextrose Agar, Malt Extract Agar and Sabouraud's Dextrose Agar). The highest number of Yeast genera was in November (6) followed by October (5), December and January (4) while the lowest number was in September (3). Eleven (11) isolates yeasts were selected randomly for in vitro sensitivity to the disinfectant agents {Chlorine, Chloroxylenol and Hydrogen peroxide (H2O2)}. All tested isolates were highly sensitive to chlorine, Chloroxylenol and H2O2. The MIC value of chlorine for most of them was 0.01 % and for Chloroxylenol was 0.1 % except Candida tropicalis and C.  glabrata. Regarding the effect of H2O2 the MIC value ranged from 0.1% - 12.8 %.
Keywords: Isolation; Yeast; Duhok City; Chlorine; Chloroxylenol